Pemanfaatan Teknologi Inovatif Dalam Pembelajara Blended Learning - Uswatun Khasanah, Uswatun Khasanah; Ririn, Ririn; Dian Sanuri, Dian Sanuri; Armiyanti, Armiyanti (Indonesian Journal of Islamic Educational Review, 2024)
This article discusses the use of innovative technology in Blended Learning. Research abstract. The method used in this article is a library method that integrates literature with relevant findings in the field. This article relies on data and material obtained from library sources, including books, journals and other literature. Data sources were obtained through the process of collecting literature to obtain theoretical information and knowledge. Data analysis techniques are carried out through the stages of summarizing, presenting data and drawing relevant conclusions. Innovative technology in blended learning has transformed education, enriching the student experience, and creating a dynamic and inclusive environment. This approach combines online and face-to-face learning, allowing students to learn at their pace and style. Technology integration increases student engagement, instructional flexibility, and access to resources, helping to achieve educational goals. Some innovative technologies that can be used to support Blended Learning learning are Learning Management Systems (LMS), Video Conferencing Tools, Gamification Tolls, Augmented Reality (AR).